Developing a Reduced 2D Model for Rotating Detonation Engine Simulations - Bonet Garcia, Genis (Cranfield University, 2025)
This thesis develops a compact, reproducible two-dimensional finite-volume Euler solver in vectorized Python to support exploratory detonation studies. The flow solver uses MUSCL reconstruction with an HLLE approximate Riemann flux and a strong-stability-preserving Runge–Kutta time integrator, emphasizing portability and clear, testable software structure. Verification exercises include a quantitative Sod shock tube study against an exact Riemann solution and a qualitative circular blast symmetry check; additional timing sweeps compare a MATLAB baseline to the vectorized Python port. Thermochemistry is designed but not exercised in the CFD results: instead, a standalone JAX-based multi reactor module is validated against Cantera and benchmarked for scaling, demonstrating increasing speedups with problem size while maintaining parity in instantaneous rates and thermodynamic conversions. Together, the results indicate close agreement with the MATLAB reference on canonical tests and credible throughput gains for batched chemistry, with an explicit path to operator-split coupling. Limitations include the absence of in-line chemistry in the delivered solver and a focus on ideal-gas mixtures; future work targets robust operator-split integration and extended verification and validation.
Keywords: Finite-volume methods; MUSCL; HLLE; operator splitting; Euler equations; Arrhenius; NASA-7; JAX; Cantera; Optimization